Biological medication in atopic dermatitis. (4th May 2022) - Fölster-Holst, Regina; Torrelo, Antonio; Das, Kinnor; Murrell, Dedee F; Patil, Anant; Rahmat Pour Rokni, Ghasem; Grabbe, Stephan; Staubach, Petra; Sohn, Anna; Goldust, Mohamad
ABSTRACT: Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disorder associated with intense itch/pruritus and skin lesions. Several modalities of treatment including topical therapy, systemic agents, and biologics are available for the treatment of disease. Despite this, management poses challenge due to chronic nature and recurrent episodes in many patients. Biologics represent an important option of treatment for patients who do not respond to the traditional treatment. Areas covered: In this article, we focused on efficacy and safety of biologics in the treatment of atopic dermatitis. Other therapies are out of the scope of this review. Articles from PubMed and Google scholar and cross references of retrieved articles were used to write the narrative review. Expert opinion: Biologics play an important role in the treatment of atopic dermatitis. Every biologic has its own place in the treatment considering pharmacological profile, efficacy, and safety. Several biologics have been studied in the treatment of moderate-to-severe cases who failed to provide adequate response to traditional treatment. Dupilumab, is approved for the treatment of moderate-to-severe atopic dermatitis. Tralokinumab and nemolizumab have shown promising results in patients with atopic dermatitis.